Accès au foncier relatif à la pisciculture familiale au Centre-Ouest et au Sud-Ouest de la Côte d’Ivoire - Aymard Boris Goulin; Adja Ferdinand Vanga; Yao Célestin Amani; Mélécony Célestin Blé; Blé Marcel Yoro (VertigO)
The context combining land saturation on the backdrop of imperfect commodification of the land, appreciation of lowlands and renewed enthusiasm for family fish farming in Central-West (CW) and Southwest (SW) of Côte d'Ivoire complicates the acquisitive and conservative mechanism of rights relating to fish farm land. This study was conducted with 213 fish farmers of whom 142 in the CW and 71 at SW as well as 34 non-fish farmer actors by proposing to describe the access modes to fish farm land in these two regions. As a result, in varying proportions, different modes are adopted for access to fish farm land. These are the donation, the purchase, the inheritance and the indirect farming (IF) through which the fish farmers guarantee perennial exploitation rights on their production sites.